Current trends in management consulting - Buono, Anthony F. (Research in management consulting ;, 2001)
Volume One in this series focuses on current trends in the management consulting industry. It is divided into three sections: (1) a look at some of the broad changes taking place in the management consulting industry, (2) an examination of recent trends and techniques in the practice of management consulting, and (3) reflections on the current state of affairs in the industry. As this brief overview has hopefully captured, the first volume in this series provides ample insight into and differing perspectives on the multi-faceted world of management consulting. Thanks are due to all the authors for their thoughtful work, good-natured colleagueship, and willingness to contribute their thoughts and insights about the consulting field. This volume would not have been possible without their efforts.